P01.19.A The temporo-parieto-occipital junction in the non-dominant hemisphere as a challenging hub for glioma surgery: functional and oncological outcomes. (5th September 2022) - Conti Nibali, M; Puglisi, G; Leonetti, A; Rossi, M; Gay, L; Sciortino, T; Mattioli, L; Gambaretti, M; Viganò, L; Bello, L
Abstract: Background: The temporo-parieto-occipital junction (TPOJ) in the non-dominant hemisphere is a complex region intersected by multiple white matter bundles (Optic radiations, Inferior-fronto-occipital tract, inferior-longitudinalis-tract, superior-longitudinalis-tract, vertical-occipital-tract, medial-dorsal-longitudinal-tract, parietal-aslant-tract), subserving several high-level neurological functions such as spatial recognition, visual agnosia, visual field, attention and working memory. Few data are available on the optimum brain mapping strategy to be adopted for resecting tumors involving this area. Ideally it should allow surgeon to effectively identify several tracts and safely preserve all functions. Material and Methods: We developed a proper protocol to approach this complex area integrating, in awake condition, intraoperative visual test (iVT) to mapping visual field, semantic association test (SRAT) to prevent visual agnosia and preserve working memory, hand manipulation task (hMT) to preserve spatial abilities. We reviewed its efficacy in a series of 38 patients with tumors involving non-dominant TPOJ, looking to functional (neurologic-neuropsychological) and oncological (EOR) outcomes. we perform a lesion symptom map and a disconnectome analysis to evaluate what region predict a decline in neuropsychological function and which tract of white brain matter are correlated in the decline of performance. Results: Feasibility was high and all patients were able to perform and complete the protocol, which lasted, on the average11 min cortically and 25 min subcortically. Specificity was >95%. Immediate post-operative deficits were documented in 87.4% of patients, permanent in 3.9% (visual field, visual spatial abilities). Attentive and emotional domains were those mostly affected in the neuropsychological evaluation. Lesion symptom mapping and disconnectomic analysis showed that the postoperative decrease in neuropsychological performance was associated with resection of a cluster of voxels corresponding to the anterior portion of the temporo-parietal junction. The white matter tracts mainly involved were the anterior and posterior segment of the middle longitudinal fasciculus (aMdLF and pMdLF) and the parietal aslant tract (PAT). Conclusion: Effective and safe resection of tumors involving non-dominant TPOJ is feasible. The adoption of a specific brain mapping protocol in awake setting is recommended to achieve a full functional preservation and extend tumor resection. Further analysis should be performed to assess the role of this subcortical tracts.